Longitudinal Surveillance of Anopheles Mosquitoes in Kulon Progo, Indonesia - Fardhiasih Dwi Astuti; Ali Sukamto; Shafira Putri Hermayanti (Borneo Scientific Publishing, 2026)
Sustaining malaria elimination requires continued surveillance in receptive areas where ecological and anthropogenic conditions may still support vector persistence. This study assessed monthly Anopheles mosquito density in Kulon Progo Regency, Indonesia, during 2023–2024 as an early warning indicator for malaria re-establishment. A descriptive longitudinal entomological surveillance study was conducted in receptive subdistricts of Kulon Progo. Adult mosquitoes were collected from 18:00 to 06:00 using indoor and outdoor human landing catches and resting collections around houses and livestock shelters. Specimens were identified morphologically, and density was expressed as Man-Hour Density (MHD). Anopheles density varied markedly by subdistrict and year. Nanggulan recorded the highest MHD in both years, increasing from 35.21 in 2023 to 69.46 in 2024. Additional measurable vector activity was detected in Kokap (MHD = 6.53) and Sentolo (MHD = 20.00) in 2024. Species data showed that Anopheles vagus was the dominant morphologically identified taxon, accounting for 84.7% of all specimens, while An. anularis, An. aconitus, An. kochi, An. barbirostris, and several low-frequency taxa were also recorded. Malaria receptivity in Kulon Progo remains heterogeneous and dynamic despite malaria-free status. Routine monthly entomological surveillance can support early detection of increased vector density and guide spatially targeted vector control. The findings should be interpreted as evidence of vector receptivity rather than confirmed transmission because sporozoite infection, vector competence, and blood-meal source were not assessed.